AI Integration in English Language Teaching: Junior High School Teachers’ Perceptions and Readiness in Ogan Ilir, South Sumatera - Susilo, Agung; Firdaus, Masagus; Yukamana, Hanni (International Journal of Research in Education, 2026)
Artificial Intelligence (AI) is increasingly reshaping educational practices worldwide, particularly in language learning. This mixed-methods study investigates English teachers’ perceptions and readiness toward AI integration in junior high schools in Ogan Ilir, South Sumatra, Indonesia, an under-resourced and largely rural context that remains underrepresented in global AI-in-education research. Guided by the Technological Pedagogical Content Knowledge (TPACK) framework and technology acceptance perspectives, the study examines how teachers’ technological competence, pedagogical readiness, and institutional conditions interact to shape AI adoption in English language teaching (ELT). Data were collected through questionnaires, interviews, and classroom observations and analyzed using descriptive statistics and thematic triangulation. The findings indicate that teachers hold generally positive view on AI and recognize its potential to enhance instructional effectiveness, student motivation, and personalized learning. However, their readiness for AI integration remains moderate, constrained by limited professional development, inadequate digital infrastructure, insufficient AI literacy, and policy-related gaps. By foregrounding teachers’ voices from a rural context, this study extends international ELT and AI-in-education scholarship beyond technologically advantaged settings. This research adds empirical support to discussions of equitable AI integration while underscoring the importance of context-specific professional development, institutional infrastructure, and ethical governance in fostering sustainable AI-mediated ELT practices.